PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN BANK INDONESIA CABANG PEKANBARU - Setiawan, Riadi; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to analyze the transformational leadership style and its influence on the performance of Bank Indonesia employees Pekanbaru Branch. Transformational leadership style as a variable (X), and employee performance as a variable (Y).The method in this research is descriptive and quantitative using SPSS 20 program, where the sample used is Bank Indonesia employee which amounted to 50 people and data collection technique through questionnaire.The results of analysis using validity test, reliability test, test of determination of simple linear regression test and t test. So it can be concluded that the leadership style transformational significant effect on the performance of Bank Indonesia employees Pekanbaru Branch.Keywords: Transformational Leadership Style, and Employee Performance